2018
DOI: 10.1590/0037-8682-0472-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inflammatory biomarkers, carotid intima-media thickness and cardiovascular risk in HIV-1 treatment-naive patients

Abstract: The majority of participants had a low CVR (94%). After reclassification, considering the CIMT percentiles, 13 (19.4%) patients had medium/ high CVR, while 54 (80.6%) patients had low CVR. The difference between the proportions of CVR when considering the CIMT and its corresponding percentile was statistically relevant. Body mass index was the only predictor of higher CVR (p = 0.03). No biomarker was found to predict CVR. People living with HIV have a high prevalence of dyslipidemia before ARV therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
1
0
1
Order By: Relevance
“…These associations rely upon correlations between markers of immune activation, such as the frequency of CD38 + HLA-DR + T lymphocytes, with atherosclerosis and CVD among both the general 16 and the HIV-1 infected population 17 20 . The same trend is observed for several inflammation markers, such as serum IL-6, IL-1β, C-reactive protein, and D-dimer levels, which are increased in HIV infection and associated with the development and severity of CVD 21 26 .…”
Section: Introductionsupporting
confidence: 68%
“…These associations rely upon correlations between markers of immune activation, such as the frequency of CD38 + HLA-DR + T lymphocytes, with atherosclerosis and CVD among both the general 16 and the HIV-1 infected population 17 20 . The same trend is observed for several inflammation markers, such as serum IL-6, IL-1β, C-reactive protein, and D-dimer levels, which are increased in HIV infection and associated with the development and severity of CVD 21 26 .…”
Section: Introductionsupporting
confidence: 68%
“…Previous studies have demonstrated that PWH on suppressive ART exhibit a pro-inflammatory immune profile even when viral loads are well below the detection level [ 4 , 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ]. HIV-1 replication persists below the detection threshold in unique bio-niches [ 18 21 ].…”
Section: Chronic Inflammation In Hiv-1 Infectionmentioning
confidence: 99%
“…Benzer şekilde ART tedavisi alan hastalarda CIMT progresyonunun araştırıldığı bir çalışmada CIMT ile hs-CRP bazal değerleri arasında pozitif korelasyon saptanmıştır 20 . D-dimer ve CIMT ilişkisinin araştırıldığı bir diğer çalışmada ise iki parametre arasında anlamlı bir ilişki saptanmamıştır 26 . Bizim çalışmamızda da CIMT ile CRP ve D-dimer arasında anlamlı bir ilişki bulunmadı.…”
Section: Introductionunclassified